STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITY THROUGH GAMIFICATION-BASED CRBL LEARNING MODEL BASED ON DIFFERENCES IN LEARNING STYLES - Ana Nikmatu Rahmah; Bambang Sri Anggoro; Abi Fadila (ZILLZELL MEDIA PRIMA, 2025)
This study aims to determine the influence of the gamification-based Creative Responsibility Based Learning (CRBL) learning model on students' mathematical creative thinking skills based on differences in learning styles. This study uses a quantitative approach with the type of research, namely quasi-experimental design and the design used, namely posttest only control group design. The population of this study is all grade VIII students of MTs Al-Hikmah Bandar Lampung for the 2024/2025 school year. The sampling technique uses cluster random sampling. The samples taken were three classes with experimental class 1 using the gamification-based CRBL learning model, experimental class 2 using the CRBL learning model and control class using the direct instruction learning model. The data collection technique uses tests and questionnaires. The hypothesis test uses a two-way anova test with the prerequisite tests, namely the normality and homogeneity test and the double comparison test using the scheffe test. The results of this study are that there is an influence of the gamification-based CRBL learning model on students' mathematical creative thinking ability, there is no influence of student learning style on students' mathematical creative thinking ability, and there is no interaction between the CRBL learning model and students' learning style on mathematical creative thinking ability.